The Lives of Machines : The Industrial Imaginary in Victorian Literature and Culture. - Ketabgian, Tamara S. (Ann Arbor : University of Michigan Press, 2011)
Expanded views of the connection between humans and machines in the Victorian era.
Intro -- Cover -- Dedication -- Acknowledgments -- Introduction -- Prosthesis -- Chapter 1: Human Parts and Prosthetic Networks: The Victorian Factory and Mesmeric Forces Chapter 1: Human Parts and Prosthetic Networks: The Victorian Factory and Mesmeric Forces -- Animal Machine -- Chapter 2: "Melancholy Mad Elephants": Affect and the Animal Machine in Hard Times Chapter 2: "Melancholy Mad Elephants": Affect and the Animal Machine in Hard Times -- Chapter 3: Brute Appetites: Labor and Leisure in Mary Barton and Early Victorian Manchester Chapter 3: Brute Appetites: Labor and Leisure in Mary Barton and Early Victorian Manchester -- Energy System -- Chapter 4: Psychic Forces: Steam, Water, and Mechanical Perception in The Mill on the Floss Chapter 4: Psychic Forces: Steam, Water, and Mechanical Perception in The Mill on the Floss -- Chapter 5: A "Musical Steam Engine": Sympathy, Technique, and Industrial Community Chapter 5: A "Musical Steam Engine": Sympathy, Technique, and Industrial Community -- Afterword -- Notes -- Bibliography -- Primary Sources: Novels and Fiction Primary Sources: Novels and Fiction -- Other Primary Sources Other Primary Sources -- Secondary Sources Secondary Sources -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books